2009
DOI: 10.1086/599123
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Infection and Cervical Cytology in HIV‐Infected and HIV‐Uninfected Rwandan Women

Abstract: Background Data on human papillomavirus (HPV) prevalence are essential for developing cost-effective cervical cancer prevention programs. Methods In 2005, 710 human immunodeficiency virus (HIV)–positive and 226 HIV-negative Rwandan women enrolled in an observational prospective cohort study. Sociodemographic data, CD4+ cell counts, and cervical specimens were obtained. Cervicovaginal lavage specimens were collected from each woman and tested for >40 HPV types by a polymerase chain reaction assay; HPV types 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
64
4
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(86 citation statements)
references
References 26 publications
(24 reference statements)
16
64
4
1
Order By: Relevance
“…Unlike in previous reports [18,19], we found no significant difference in the prevalence of multiple genotypes by HIV status. While this could be attributed to our small sample size, recent studies have also shown that advances in technology and improved DNA extraction protocols have resulted in increased detection of HPV genotypes [20], and therefore the unmasking of the role played by previously underestimated genotypes.…”
Section: Discussioncontrasting
confidence: 99%
“…Unlike in previous reports [18,19], we found no significant difference in the prevalence of multiple genotypes by HIV status. While this could be attributed to our small sample size, recent studies have also shown that advances in technology and improved DNA extraction protocols have resulted in increased detection of HPV genotypes [20], and therefore the unmasking of the role played by previously underestimated genotypes.…”
Section: Discussioncontrasting
confidence: 99%
“…cation of branch E, it may represent the most widely spread variant. The same E6 and L1 sequences were also found in Europe (Germany) (21), Africa (Rwanda) and North America (Costa Rica) (11,22,23). We speculate that this variant may be derived from the worldwide migration of the European host.…”
Section: Resultssupporting
confidence: 64%
“…The prevalence of HPV was significantly higher in the HIV positive group and adjusted for age (25-34 years 75% vs 29%; 35-44 years 64 vs 7%; 45-54 years 57% vs 13% and over 55 years 38% vs 0%) [47]. In addition 46% of HIV positive women had high-risk types of HPV and 35% were infected with multiple types and in turn, this was associated with higher risk of abnormal cytological findings.…”
Section: Hpv Dna Testingmentioning
confidence: 90%
“…There is good evidence provided by randomised placebocontrolled trials that these vaccines prevent both persistent infection with the types included in the vaccines, as well as pre-invasive lesions of the anogenital tract associated with the types present in the vaccines [47][48][49][50][51][52][53].…”
Section: Primary Prevention Of Cervical Cancer: Hpv Vaccinesmentioning
confidence: 99%